2015
DOI: 10.1007/s11356-015-5574-4
|View full text |Cite
|
Sign up to set email alerts
|

Using air, soil and vegetation to assess the environmental behaviour of siloxanes

Abstract: This study aimed to contribute to the enhancement of the knowledge of levels, trends and behaviour of eight siloxanes (four linear and four cyclic) in the environment. Adding to the prioritised scrutiny of the incidence in the atmosphere through passive samplers (sorbentimpregnated polyurethane foam disks-SIPs), the sampling of pine needles and soil was also performed, thus closing the circle of atmospheric exposure in the areas of study. Two sampling campaigns (one in summer and one in winter) were done in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The clear predominance of cVMSs over lVMSs verified in all samples considered in this study is consistent with the results on the determination of siloxanes in biota samples in marine environments (Kaj et al, 2005;Warner et al, 2010;Hong et al, 2014;Jia et al, 2015), as well as in terrestrial vegetation (pine needles) in Portugal (Ratola et al, 2016). Besides, these results are also in line with the prevalence of cyclomethicones use in wash-off PCPs, mostly D5 and D6, and the resulting higher mass loadings of these compounds to WWTPs when compared to lVMSs (van Egmond et al, 2013;Xu et al, 2013;Capela et al, 2016a), suggesting that these facilities are one of the possible route of these pollutants into coastal environments.…”
Section: Mediterranean Coastline Of Marseille South Francesupporting
confidence: 92%
See 2 more Smart Citations
“…The clear predominance of cVMSs over lVMSs verified in all samples considered in this study is consistent with the results on the determination of siloxanes in biota samples in marine environments (Kaj et al, 2005;Warner et al, 2010;Hong et al, 2014;Jia et al, 2015), as well as in terrestrial vegetation (pine needles) in Portugal (Ratola et al, 2016). Besides, these results are also in line with the prevalence of cyclomethicones use in wash-off PCPs, mostly D5 and D6, and the resulting higher mass loadings of these compounds to WWTPs when compared to lVMSs (van Egmond et al, 2013;Xu et al, 2013;Capela et al, 2016a), suggesting that these facilities are one of the possible route of these pollutants into coastal environments.…”
Section: Mediterranean Coastline Of Marseille South Francesupporting
confidence: 92%
“…Considering that some of the emission routes of these compounds are through WWTPs discharges and the common use of siloxanes in PCPs formulations, marine and coastal environments are potential hotspots for the presence of VMSs, especially considering the high anthropogenic pressure and the increased use of protective PCPs in the summer months with the rise of the temperature and the exponential growth of tourism. Ratola et al (2016) found much higher levels of VMSs in the air of one beach from the south of Portugal in summer than in winter. Monitoring the distribution levels of VMSs in such areas is therefore very important, and to date there is not much information available on the distribution, fate and trends of siloxanes in marine environments in Southern European latitudes.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, much lower levels (maximum 8 ng/m 3 ) were observed at urban and industrial sites in Portugal. 12 Atmospheric ΣVMS levels in Turkey ranged between 12.7 and 212 ng/m 3 at an urban site in Izmir, 31 while a range of 41.7 to 433 ng/m 3 was measured in the Kucuk Menderes river basin. 32 Shoeib et al 33 measured VMS concentrations in the vicinity of a WWTP and reported elevated average atmospheric cVMS concentrations, 3000 ± 730 and 1700 ± 170 ng/m 3 during summer and winter periods, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Samples from the urban area and the remote area had levels of D4 of 583 ngSIP and 35.4 ngSIP in the air samplers and concentrations of D4 of 1.3 ng/g dw and 0.40 ng/g dw in the pine needles, respectively. These techniques were employed for a larger scale study that collected samples from urban areas (N=2), industrial parks (N=2), beach resorts (N=2), and remote areas of Portugal (Ratola et al, 2016). In air samples (N=32), concentrations of D4 ranged from 0.6 to 7.8 ng/m 3 , with D4 contributing a mean of 21% of the total concentration.…”
Section: Data Screening (Title/abstract)mentioning
confidence: 99%